(untitled) (Fiep Bulletin - online, 2013)
One of the great challenges of the twenty-first century education focuses on training of professionals beyond the accumulation of knowledge to transform them, contextualize them and adapt them to current reality. So, think about the training of future teachers of Physical Education, higher goal of this work, stumbles into a very important point that is the paradigm shift of Education. Since paradigms such structures are "crucial not only in the way of conceiving education, but to act educationally, emphasizes the validity is to know about them and reflect on them under penalty of having serious restrictions in the realization of a practical teaching sector. This study finds support in Assmann (1994), Behrens (2005), Capra (1995), Crema (1995) and Freire (1997) among others, to support the conduct of the literature search. And after these readings found that many proposals assist the teaching of Physical Education and that the so-called Innovative Education Paradigms are able to ensure an action consistent with the current aspects of education. Still occurs, a co-existence of different approaches, showing that each work tends to mean re-scientific theories and assign them to their historical and socially constructed conceptions. When teacher trainer for teachers of Physical Education, before these new paradigms, it rebuild roads that rescue the pleasure in work, education and life through the perspective of competence, creativity and commitment.